Pengembangan E-Modul Berbasis Flipbook Terhadap Kemampuan Pemecahan Masalah Matematis Pada Materi Bentuk Akar - Vlorenta Prisilla Wiwin; Dewi Risalah; Yudi Darma (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This discussion is to determine the results of the flipbook-based E-Module on the ability to solve mathematical problems in root form material in class This discussion applies the ADDIE development design form, which has 5 main stages, namely analysis, design, development, implementation, evaluation. The subjects of this discussion are 23 students in class X at SMK Mandiri Pontianak. In this discussion, the instruments used are validation sheets, questionnaires and pretest posttest questions. The first research result is the validation of the E-Module, which means the average score for the 3 experts is 87.66% according to very valid criteria. The second is the practicality value, based on views through questionnaire scores filled in by teachers & students which are accumulated to reach a percentage of 83% according to very practical criteria. Then the effectiveness is checked through the results of inferential statistical tests using the student's pretest and posttest according to the results of the t-test, namely tcount < - ttable significant α=5% (a=0.05). Significant differences were found in student learning outcomes and mathematical problem solving abilities, so that the E-Module was categorized as effective. Therefore, it can be concluded that the flipbook-based E-Module for mathematical problem solving abilities in root form material in class.